Evaluation of Prenatal and Perinatal Features in Children Diagnosed with Autism Spectrum Disorder: Is There a Gender Difference? - Yazıcı, İpek Perçinel (Galenos Publishing House, 2020)
Objectives: In this study, it was aimed to retrospectively evaluate prenatal and perinatal features in children with autism spectrum disorder (ASD). Materials and Methods: The data of the children who applied to our outpatient clinic between 01.01.2018 and 31.12.2019 and who were between the ages of 12 and 72 months were examined retrospectively. The children who were diagnosed with ASD and the children who were not diagnosed with neurodevelopmental disorder (control group) were compared in terms of pre/perinatal features. Results: From prenatal features; maternal and paternal age during pregnancy, difference between the age of parents, maternal medical illness during pregnancy, threatened abortion, negative life events and maternal smoking/medication during pregnancy were significantly higher in children with ASD. From perinatal features; low birth weight, preterm delivery, labor difficulties, cesarean section, hypoxia/asphyxia, and incubator/intensive care history were significantly higher in ASD than in the control group. In the analysis conducted considering gender in the ASD group; maternal and paternal age, labor difficulties, hypoxia/asphyxia history and incubator/intensive care history were significantly higher in boys than in girls. Conclusion: In our study, it was found that there were more prenatal and perinatal difficulties in children with autism than in those without autism. It is noteworthy that apart from the advanced age of parents, the difference in the ages of parents was significantly higher in the group with autism. In addition, it appears to be worth investigating when interpreted in conjunction with current literature findings that some pre/ perinatal features are significantly higher in boys than in girls in ASD. © Telif Hakkı 2020 Türkiye Çocuk ve Genç Psikiyatrisi Derneği / Çocuk ve Gençlik Ruh Sağlığı Dergisi, Galenos Yayınevi tarafından yayınlanmıştır.
Otizm Spektrum Bozukluğu Tanılı Olgularda Prenatal ve Perinatal Özelliklerin Değerlendirilmesi: Cinsiyet Farklılığı Var Mı?
Keywords: autism; Children; gender; perinatal; prenatal